2012
DOI: 10.1590/s1984-70332012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition as related to seed color of common bean

Abstract: -This study aimed to quantify the levels of protein and minerals in common bean

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
71
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 18 publications
22
71
4
2
Order By: Relevance
“…Beans are also important sources of minerals, especially iron, with concentrations ranging from 8.90 to 161.50 mg kg -1 dry matter (DM), and zinc, with concentrations ranging from 19.00 to 65.50 mg kg -1 DM (Talukder et al, 2010;Tryphone & Nchimbi-Msolla, 2010;Silva, Abreu, Ramalho, & Maia, 2012a), in common bean cultivars. In addition, common bean grains do not require polishing or any other prior mechanical processing and thus can be considered a whole food.…”
Section: Introductionmentioning
confidence: 99%
“…Beans are also important sources of minerals, especially iron, with concentrations ranging from 8.90 to 161.50 mg kg -1 dry matter (DM), and zinc, with concentrations ranging from 19.00 to 65.50 mg kg -1 DM (Talukder et al, 2010;Tryphone & Nchimbi-Msolla, 2010;Silva, Abreu, Ramalho, & Maia, 2012a), in common bean cultivars. In addition, common bean grains do not require polishing or any other prior mechanical processing and thus can be considered a whole food.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of wheat, the color of the seed affects the yield and quality of the flour (Kuraparthy et al 2008); in Brassica rapa the yellow seeds have a thinner covering which also contributes to 5-7% more oil and flour as well as a greater amount of protein (Rahman et al 2007). In the black lines of Phaseolus vulgaris the protein content, iron and zinc are higher, in lines of other colors are richer in calcium, while the "carioca" is high in magnesium and manganese (Silva et al 2012). For the case of sesame, color is an important aspect as it is associated with biochemical properties, antioxidants and resistance to diseases (Zhang et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Using lines from the germplasm banks of institutions that work with genetic breeding of the common bean, many studies have demonstrated genetic variability in the traits that confer nutritional quality to the common bean and their modulation by the environment (Beebe et al, 2000;Mesquita et al, 2007;Ribeiro et al, 2008;Silva et al, 2012;Zacharias et al, 2012). Silva et al (2012) evaluated 100 lines from the germplasm bank of the Federal University of Lavras (UFLA) and observed high variability in calcium content.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2012) evaluated 100 lines from the germplasm bank of the Federal University of Lavras (UFLA) and observed high variability in calcium content. However, the lines identified as having the greatest calcium content are typically poorly adapted and/or have agronomic characteristics and grain types that are not in agreement with the preferences of the consumers and farmers.…”
Section: Introductionmentioning
confidence: 99%